Pathogenic characterization of Phialophora submersa, a new black yeast isolated from freshwater sediments in Spain - Fernández-Bravo, Ana; Camuña-Pardo, Laura; Sanchis, Marta; Ahmiane, Youssef; Capilla, Javier; Gené, Josepa (Frontiers in Cellular and Infection Microbiology, 2025)
Phialophora submersa is a recently described black yeast species (Chaetothyriales), isolated from freshwater sediments in Catalonia (Spain). It is closely related to P. americana and P. verrucosa, two opportunistic pathogens known to cause subcutaneous infections in humans and animals. This study investigates the pathogenic potential of P. submersa, its in vitro susceptibility to clinically relevant antifungal agents, and its response to various cellular stressors. Using a murine macrophage (J774A.1) infection model, we evaluated phagocytosis, intracellular survival, cell damage, and the expression of six immune-related genes (TNF-α, CCL20, RELA, TP53, NLRP3, IL-1β), in comparison with P. americana and P. verrucosa. The results showed that P. submersa induced higher phagocytosis rates in murine macrophages than the P. verrucosa, although lower than P. americana. Cell damage, intracellular survival, and expression of the immune-related genes were higher after macrophage infection with P. verrucosa than with P. submersa and P. americana, which exhibited comparable profiles. All three species displayed similar antifungal susceptibility profiles, being susceptible to most azoles (except fluconazole), terbinafine, and echinocandins (with reduced efficacy against P. verrucosa), but showed moderate resistance to flucytosine, amphotericin B, and olorofim. The resistance of P. submersa to stress was strain-dependent, with only one strain exhibiting notable resistance to multiple stressors. This research provides new insights into the biology of P. submersa, including its potential as a human pathogen, and the molecular factors that could drive an infection process.